Overexpression of miRNA-3613-3p Enhances the Sensitivity of Triple Negative Breast Cancer to CDK4/6 Inhibitor Palbociclib - Yu, Yuanhang; Liao, Han; Xie, Rong; Zhang, Yue; Zheng, Renjing; Chen, Jianying; Zhang, Bo (Frontiers in Oncology, 2020)
Triple negative breast cancer (TNBC) is characterized by lack of expression of the estrogen and progesterone receptors and HER2, which are common therapeutic targets. CDK4/6 inhibitor Palbociclib has been approved as an anti-cancer agent for breast cancer. However, identification of biomarkers predictive of response to Palbociclib has been challenges in the molecular targeted therapy. In this study, we identify microRNAs as a hallmark in TNBC patients, and explore if miR-3613-3p might serve as a tumor suppressor biomarker for triple negative breast cancer patients and if overexpression of miR-3613-3p could enhance the sensitivity of TNBC cells to Palbociclib. We show that miR-3613-3p expression was downregulated in TNBC tumors and cells and the overexpression of miR-3613-3p in patients' tumor tissues was clinically and pathologically correlated with favorable prognosis, such as the smaller tumor size and the lower Ki-67 Li. In vitro, overexpression of miR-3613-3p suppressed cell proliferation and induced G1 cell-cycle arrest and enhanced the sensitivity of TNBC cells to Palbociclib treatment in vivo. In vivo study revealed that overexpression of miR-3613-3p inhibited TNBC tumorigenesis and exerted a significant inhibitory effect of Palbociclib on MDA-MB-231 cells. SMAD2 and EZH2 were found to be two direct targets of miR-3613-3p, and mediate the proliferation of TNBC cells and the sensitivity of the cells to Palbociclib through inducing cellular senescence. Our findings suggest that miR-3613-3p acts as a cancer-suppressor miRNA in TNBC. Moreover, our study showed that overexpressing miR-3613-3p might be used as a predictive biomarker for the response of TNBC to Palbociclib.